The Criminal Procedural Program in 19th-century Constitutions: A brief historical review of jury trials in Peru - Noronha Val, Diego Alonso (2024)
The criminal process is built upon the Constitution. Its legal regulation is not independent but arises inevitably from the fundamental norm of the State. It is precisely within this instrument that the general framework of principles is established, from which the specific rules governing the criminal process in a nation are derived. This theoretical core is referred to in Hispanic-American doctrine as the Procedural Criminal Program of the Constitution, and in Portuguese doctrine as the Procedural Criminal Constitution. It emerged in the 1980s, coinciding with the paradigm shift brought by the Spanish Constitution of 1978, and was later debated in Peru with the 1993 Constitution. In this context, it is logical that there are no research studies aimed at analyzing the historical procedural criminal program in national constitutions. Thus, this manuscript seeks to explore part of the procedural criminal program that developed during the 19th century in Peru, with a particular focus on the institution of trial by jury, a topic rarely addressed by national doctrine due to its ineffective implementation during that period. This text does not aim to provide an exhaustive analysis but rather an introduction to the concepts of the procedural criminal program of the Constitution and trial by jury, intended to promote their investigation and historical analysis.